Association between the dry-land strength & power and the kick start kinetics in elite male and female swimmers - Santos, C. C.; Barbosa, T. M.; Marinho, D. A.; Costa, M. J. (Sports Biomechanics, 2022)
The aim of this research was to determine the association between dry-land exercises and the start kinetics in elite swimmers. Fourteen swimmers (eight males and six females) included in a national team took part in this study. A fixed smith-machine was used to measure the maximal full squat strength (Smax). The height of squat (SJ) and countermovement (CMJ) jumps were collected with a contact mat. The ground reaction force of the kick starts in the three-dimensional axis (Fz horizontal; Fy, vertical; Fx, lateral) was obtained by an instrumented force plate in the starting block. Overall, the Smax showed a high and significant association with Fz (r = 0.60) and Fy (r = 0.87). Moderate and significant associations were found between Fy and SJ (r = 0.51) and CMJ (r = 0.57). While Smax in males showed high association with Fy (r = 0.77), the Smax for females showed greater association with Fz (r = 0.84). As conclusion, the full back squat seems to be the dry-land exercise with higher association with the kick start kinetics. While in males the full squat defines better the vertical component, for females it defines the horizontal one.